From the bulk electrolyte solution to the electrochemical interface - Cachet, H. (Condensed Matter Physics, 2017)
This paper is aiming at presenting some relevant contributions of Jean-Pierre Badiali during the first ten years
of his growing scientific activity. This presentation does not contain new materials but is based on a number
of selected papers published in the seventies, a part of them written in French. The presentation is organized
around three points. The first point, corresponding to his PhD thesis, is concerned with the study of ion-solvent
and ion-ion interactions in a solution using complex dielectric permittivity measurements in the Hertzian and
microwave frequency range. The second one is concerned with an analysis of the ion pair absorption band
observed in the far infrared region in terms of an interionic potential energy. The third one is concerned with
the metal-solution interface and his significant advances on (i) the Lippmann equation linking electrocapillary
and electrical measurements and (ii) the contribution of the metal to the differential interfacial capacity. Метою статтi є представлення важливого внеску Жана-П’єра Бадiалi впродовж перших десяти рокiв його стрiмкої наукової дiяльностi. Вона не мiстить нового матерiалу, проте базується на низцi вибраних
статтей, опублiкованих в 70-х роках, частина з яких написана французькою мовою. Стаття представляє
три аспекти. Перший, що вiдповiдає тематицi дисертацiї доктора фiлософiї, присвячений вивченню взаємодiй “iон-розчинник” та “iон-iон” в розчинi з використанням складних вимiрювань дiелектричної проникностi в дiапазонi Герцiв i мiкрохвильових частот. Другий аспект стосується аналiзу зони поглинання
iонних пар, яка спостерiгається в далекiй iнфрачервонiй областi в термiнах мiжiонної потенцiальної енергiї. Третiй пов’язаний з поверхнею роздiлу “метал-розчин”, i важливими досягненнями тут є: (i) рiвняння
Лiппмана, яке пов’язує електрокапiлярнi та електричнi вимiрювання; (ii) внесок металу в диференцiальну
iнтерфейсну електричну ємнiсть.